2020
DOI: 10.1101/2020.08.31.275719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Cell Entry Factors ACE2 and TMPRSS2 are Expressed in the Pancreas but are Not Enriched in Islet Endocrine Cells

Abstract: Summary/AbstractReports of new-onset diabetes and diabetic ketoacidosis in individuals with COVID-19 have led to the hypothesis that SARS-CoV-2, the virus that causes COVID-19, is directly cytotoxic to pancreatic islet β cells. This model would require binding and entry of SARS-CoV-2 into host cells via cell surface co-expression of ACE2 and TMPRSS2, the putative receptor and effector protease, respectively. To define ACE2 and TMPRSS2 expression in the human pancreas, we examined six transcriptional datasets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 76 publications
2
35
2
Order By: Relevance
“…Our results indicate that ACE2 is expressed also in the pancreatic islets, and this expression is mostly located in b-cells as compared to a-cells. These results are in contrast with the two recent preprint manuscripts (57,58) which failed to observe ACE2 expression in pancreatic islet endocrine cells. Such discrepancies may be explained by a resulting sum of differences in primary antibodies sensitivity, different epitopes targeted, tissue sections preparation and pretreatment, as well as immunodetection methodology sensitivity (immunohistochemistry vs. immunofluorescence).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that ACE2 is expressed also in the pancreatic islets, and this expression is mostly located in b-cells as compared to a-cells. These results are in contrast with the two recent preprint manuscripts (57,58) which failed to observe ACE2 expression in pancreatic islet endocrine cells. Such discrepancies may be explained by a resulting sum of differences in primary antibodies sensitivity, different epitopes targeted, tissue sections preparation and pretreatment, as well as immunodetection methodology sensitivity (immunohistochemistry vs. immunofluorescence).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, a pancreatic islet local vascular damage and inflammation due to SARS-CoV-2 direct infection of ACE2 + pancreatic pericyte cells is a potential contributory factor for islet dysfunction. Of note, two recent preprint manuscripts also indicated the presence of ACE2 expression in pancreatic microvasculature (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that ACE2 is expressed also in the pancreatic islets and this expression is mostly located in β-cells as compared to α-cells. These results are in contrast with the two recent preprint manuscripts (56,57) which failed to observe ACE2 expression in pancreatic islet endocrine cells. Such discrepancies may be explained by a resulting sum of differences in primary antibodies sensitivity, different epitopes targeted, tissue sections preparation and pre-treatment, as well as immunodetection methodology sensitivity (immunohistochemistry vs. immunofluorescence).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, a pancreatic islet local vascular damage and inflammation due to SARS-CoV-2 direct infection of ACE2 + pancreatic pericyte cells is a potential contributory factor for islet dysfunction. Of note, two recent preprint manuscripts also indicated the presence of ACE2 expression in pancreatic microvasculature (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ACE2 in the pancreas is a matter of debate and contradictory results have been reported. For example, three different studies showed a higher expression of ACE2 in the exocrine duct cells than in the islets [17][18][19] , whereas another study showed that ACE2 is preferentially expressed by beta-cells 15 . By single cell sequencing, we have shown that in pancreata from mice, both DPP4 and ACE2 are highly expressed in delta-cells followed by betaand alpha-cells (unpublished data, NATMETAB-A20093633).…”
mentioning
confidence: 99%